The Role of Cooperatives in Fishermen's Empowerment for Sustainable Fisheries Development in Konawe Regency Southeast Sulawesi Indonesia - Nalefo, La; Taufik, Yani; Fausayana, Ine; Djuhasin, Abdul Rahman (Journal of Posthumanism, 2024)
Fishermen’s cooperatives play a pivotal role in empowering local fishing communities and advancing sustainable fisheries development. This study examines the contributions of cooperatives toward improving fishermen’s welfare and supporting the long-term sustainability of the fisheries sector in Konawe Regency.Using a qualitative research approach, data were collected through interviews, observations, and document analysis involving cooperatives managing fishing facility assistance. The findings reveal that these cooperatives significantly contribute by providing access to production facilities, capital, skills development, and fishery product marketing. Furthermore, they serve as collaborative platforms that promote sustainable fishery resource management by encouraging the use of environmentally friendly fishing gear and overseeing responsible fishing practices.Despite these positive contributions, several challenges hinder the effectiveness of cooperative operations, including limited managerial capacity and restricted access to broader markets. To address these issues, robust support from the government and relevant stakeholders is critical.By strengthening the institutional and operational capacity of fishermen’s cooperatives, Konawe Regency can achieve sustainable fisheries development while ensuring meaningful improvements in the livelihoods of its fishing communities.